VULNERABILITES AND MITIGATION IN COMMUNICATION SYSTEM FOR GRID INTEGRATION OF WIND ENERGY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This paper provides the `concept of communication system challenges in power grid integration .The scada has been used as communication,fault diagnosis ,though the reliability of communication with scada in drastic environment but the problems to faced such as security ,policy, system network problems are in online internet facility. We discuss all the SCADA vulnerabilities in this paper they are attributable to the lack of a well-developed and meticulously practiced security policy also we provide some mitigation of SCADA system which is ongoing process.